Continuous Control Set Model Predictive Control for Polysolenoid Linear Motor - et. al., Nguyen Hong Quang, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, a model predictive control (MPC) based on the properties of the voltage source inverter is applied to Polysolenoid motors. Polysolenoid motors are a particular type of permanently excited synchronous motor. It has a tubular texture. On the stator of the motor, there are only two windings. Based on the structural characteristics of the motor, the used source is a two-phase voltage source inverter. When considering the voltage supplied to the two windings from the inverter as continuous, the continuous control set model predictive control (CCS-MPC) is developed at the force loop. Simulation results are performed to illustrate the performance of the implemented system.